2021
DOI: 10.1002/mp.15134
|View full text |Cite
|
Sign up to set email alerts
|

Tomography of dark‐field scatter including single‐exposure Moiré fringe analysis with X‐ray biprism interferometry—A simulation study

Abstract: In this work we present tomographic simulations of a new hardware concept for X-ray phasecontrast interferometry wherein the phase gratings are replaced with an array of Fresnel bi-prisms, and Moiré fringe analysis is used instead of "phase stepping" popular with grating-based setups.Methods: Projections of a phantom consisting of four layers of parallel carbon microfibers is simulated using wave optics representation of X-ray electromagnetic waves. Simulated projections of a phantom with preferential scatter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
(209 reference statements)
0
3
0
Order By: Relevance
“…In our previous paper, 32 we performed simulations using wave optics to evaluate X‐ray phase‐contrast imaging with grating interferometry using phase stepping and with bi‐prism interferometry using single‐exposure Moiré fringe analysis. Results of reconstructed vector coefficients of small‐angle scatter showed that bi‐prism interferometry with single‐exposure Moiré fringe analysis has an increase in noise compared to grating interferometry using phase stepping because of one‐eighth the number of projection samples but provides better contrast‐to‐noise ratio (CNR) due to better photon flux with less dose and faster acquisition times.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous paper, 32 we performed simulations using wave optics to evaluate X‐ray phase‐contrast imaging with grating interferometry using phase stepping and with bi‐prism interferometry using single‐exposure Moiré fringe analysis. Results of reconstructed vector coefficients of small‐angle scatter showed that bi‐prism interferometry with single‐exposure Moiré fringe analysis has an increase in noise compared to grating interferometry using phase stepping because of one‐eighth the number of projection samples but provides better contrast‐to‐noise ratio (CNR) due to better photon flux with less dose and faster acquisition times.…”
Section: Discussionmentioning
confidence: 99%
“…In our work we performed simulations evaluating the model of [8], [67] with the reconstruction of coefficients for a fixed basis set of 7 vectors. The coefficients were reconstructed from Moiré fringe analysis of single-exposure dark-field projections obtained from X-ray bi-prism interferometry [69]. Wieczorek et al [12] modified the forward model [8], [67] to develop an anisotropic X-ray dark-field tomography (AXDT) method by replacing the discretization of the scatter function as a fixed basis set of vectors at each voxel with a spherical harmonic expansion.…”
Section: Helmholtz Decompositionmentioning
confidence: 99%
“…In our previous work we performed simulations evaluating the reconstruction of the coefficients for a fixed basis set of 7 vectors from Moiré fringe analysis of projections of a single-exposure of dark-field scatter obtained from X-ray bi-prism interferometry [69]. To obtain a tensor representation would have involved performing a second step of fitting the estimated vector coefficients to an ellipsoidal representation of the tensor at each voxel [8], [67].…”
Section: ) Diffusion Tensor Tomography Magnetic Resonancementioning
confidence: 99%